Studies on Photochromism of Primary Silver Dithizonate Complex - F.R. Fouda, Mohammad; E.D. Higazy, Hosam; M. El-Desoky, Moustafa; S. Amin, Rawhya (Asian Journal of Chemistry, 2010)
The effect of monochromatic illumination for primary silver dithizonate complex on the photo-induced current was studied. The study showed that a violet colouration of the complex was developed out, and returned again in dark to its original orange-red colouration after a time depending on complex temperature. The creation of partially or completely positive charge on one of the nitrogen atoms due to formation of covalent bonding between it and silver ion instead of coordination one, upon illumination, leads to great increase in the induced photocurrent values. The results showed that the non irradiated complex has a tetrahedral configuration, whereas the irradiated one has a distorted square pyramidal structure and has also a bivalent silver ion.